2020
DOI: 10.1016/j.bja.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of incidence of anaphylaxis between sugammadex and neostigmine: a retrospective multicentre observational study

Abstract: Background: Although cases of anaphylaxis caused by sugammadex have been reported, its incidence remains uncertain. Conversely, no studies have evaluated the incidence of anaphylaxis to neostigmine. Methods: This was a retrospective multicentre observational study of patients who underwent surgery under general anaesthesia between 2012 and 2016 to compare the incidence of anaphylaxis with sugammadex with that of neostigmine at four tertiary hospitals in Japan. To ensure the quality of diagnosis, only cases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 34 publications
1
64
1
4
Order By: Relevance
“…In addition, the NMBA-sugammadex complex can be removed via standard dialysis techniques [82]. Concern exists over hypersensitivity reactions following sugammadex administration [83]; however, the overall incidence of such events remains low and rarely impacts routine clinical care [84]. While not currently widely used in the critical care setting, its use may expand as new evidence emerges describing its use as a rescue therapy for residual blockade [85] and its role in reducing the incidence of reintubation [86] and promoting enhanced recovery protocols in the ICU [87].…”
Section: Sugammadexmentioning
confidence: 99%
“…In addition, the NMBA-sugammadex complex can be removed via standard dialysis techniques [82]. Concern exists over hypersensitivity reactions following sugammadex administration [83]; however, the overall incidence of such events remains low and rarely impacts routine clinical care [84]. While not currently widely used in the critical care setting, its use may expand as new evidence emerges describing its use as a rescue therapy for residual blockade [85] and its role in reducing the incidence of reintubation [86] and promoting enhanced recovery protocols in the ICU [87].…”
Section: Sugammadexmentioning
confidence: 99%
“…The mechanism of action of sugammadex is 10 times faster than neostigmine and has lesser side effects. In a multicenter study comparing the incidence of anaphylaxis between sugammadex and neostigmine, it was stated that neostigmine may be safer than sugammadex and it may be beneficial to revise the choice of reversal agents by anesthesiologists (3) . In the same study, it was reported that six of 29962 patients (0.02%) developed anaphylaxis due to sugammadex, and no patient had anaphylaxis due to neostigmine (0/3157) (3) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that allergic reactions due to sugammadex are more common at high clinical doses (16-96 mg kg -1 ) (9) . However, cases of anaphylaxis related to sugammadex use at low doses (1.9-2.2-1.2 mg kg -1 ) have been also reported (3,10) . In this case, the dose of sugammadex was 200 mg (2.6 mg kg -1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugammadex is a selective relaxant-binding agent developed for rapid reversal of non-depolarizing neuromuscular blockade from rocuronium 7 . Anaphylaxis is a known but rare complication of the administration of sugammadex 8 and occurs in 0.036% of cases. When it occurs urgent re-intubation is necessary.…”
Section: Discussionmentioning
confidence: 99%